2013
DOI: 10.1538/expanim.62.219
|View full text |Cite
|
Sign up to set email alerts
|

Infertility Associated with Meiotic Failure in the <i>tremor</i> Rat (<i>tm/tm</i>) is Caused by the Deletion of <i>Spermatogenesis Associated 22</i>

Abstract: The tremor rat is an autosomal recessive mutant exhibiting sterility with gonadal hypoplasia in both sexes. The causative mutation tremor (tm) is known as a genomic deletion spanning >200 kb in Chr 10q24. Spermatogenesis associated 22 (Spata22) has been shown to be a vertebrate-specific gene essential for the progression of meiosis through prophase I and completion of chromosome synapsis and meiotic recombination using a mouse repro42 mutant carrying an N-ethyl-N-nitrosourea (ENU)-induced nonsense mutation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…TRM/Kyo rats, homozygous for the tremor ( tm ) mutation, were derived from a mutant showing body tremors and curled hair found in an outbred colony of Kyo:Wistar rats at the Institute of Laboratory Animals, Graduate School of Medicine, Kyoto University in 1980 [ 16 ]. The tm mutation was identified as a ~240-kb genomic deletion on rat chromosome 10, of which 13 genes have been mapped [ 17 , 18 ]. However, tremor resistant TRMR/Kyo rats, a substrain of TRM/Kyo, were found not to develop body tremors despite carrying the tm deletion.…”
Section: Introductionmentioning
confidence: 99%
“…TRM/Kyo rats, homozygous for the tremor ( tm ) mutation, were derived from a mutant showing body tremors and curled hair found in an outbred colony of Kyo:Wistar rats at the Institute of Laboratory Animals, Graduate School of Medicine, Kyoto University in 1980 [ 16 ]. The tm mutation was identified as a ~240-kb genomic deletion on rat chromosome 10, of which 13 genes have been mapped [ 17 , 18 ]. However, tremor resistant TRMR/Kyo rats, a substrain of TRM/Kyo, were found not to develop body tremors despite carrying the tm deletion.…”
Section: Introductionmentioning
confidence: 99%
“…Drosophilia HDM (Hold'em) encodes an OB-fold protein related to RPA70 that is required for a majority of crossover and interacts with the joint-molecule resolving endonuclease complex, MEI9 -ERCC1 -MUS312 (Joyce et al 2009). In mammals, the RPA1-related MEIOB protein and associated factor, SPATA22, form an RPA-associated complex that is required for intermediate steps of recombination and normal synapsis (La Salle et al 2012;Ishishita et al 2013Ishishita et al , 2014Luo et al 2013;Souquet et al 2013). MEIOB -SPATA22 is inferred to act after initial strand exchange, perhaps to promote strand annealing in both SDSA and dHJ pathways, acting analogously to the budding yeast Rad52 protein Luo et al 2013).…”
Section: Recombination-associated Dna Synthesismentioning
confidence: 99%
“…We showed that expression of Spata22 is predominantly restricted to germ cells of both sexes, and that the SPATA22 protein is absent in repro42 mutant gonads. repro42 mutant mice and Spata22 -deficient rats display severe gonadal hypoplasia caused by arrest during prophase I of meiosis (Ishishita et al , 2013; La Salle et al , 2012). Progression through meiosis is halted due to aberrant SC formation, chromosome asynapsis and impaired DSB repair.…”
Section: Introductionmentioning
confidence: 99%